2022
DOI: 10.3390/microorganisms10040697
|View full text |Cite
|
Sign up to set email alerts
|

Putrescine Production by Latilactobacillus curvatus KP 3-4 Isolated from Fermented Foods

Abstract: Polyamines are aliphatic hydrocarbons with terminal amino groups and are essential for biological activities. It has been reported that polyamines have health-promoting effects in animals, such as the extension of lifespan by polyamine intake. The identification of a high polyamine-producing bacterium from foods could lead to the development of a novel probiotic candidate. We aimed to identify high polyamine-producing bacteria from food, and isolated and collected bacteria from vegetables and fermented foods p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Lactobacillus fermentation significantly increases pyroglutamic acid content [ 68 ]. The Latilactobacillus curvatus KP 3–4 increases putrescine concentration in the feces of germ-free mice [ 69 ]. Probiotics substantially increase the concentration of 5-hydroxyindole-3-acetic acid [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactobacillus fermentation significantly increases pyroglutamic acid content [ 68 ]. The Latilactobacillus curvatus KP 3–4 increases putrescine concentration in the feces of germ-free mice [ 69 ]. Probiotics substantially increase the concentration of 5-hydroxyindole-3-acetic acid [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that dietary supplementation with Lactobacillus spp. influences amino acid metabolism [ 67 , 68 , 69 , 72 ]. The energy metabolism was substantially enhanced, and glycolysis/gluconeogenesis pathways were inhibited in G0D30 compared to those in G1D30 in the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…There has been no such study where the investigation focused on the presence of beneficial microbes in liquor, where mainly we have focused on environment-related branded liquor starters. Previous studies have demonstrated the role of Weisslia cibaria, Weissella paramesenteroides, Pediococcus acidilactici, and Lactobacillus curvatus probiotic functions [28][29][30][31][32], which provides a base for our current study focus on the identification of the beneficial microbes in environment-related branded liquor starter. The present study identified various bacterial and fungal species which are beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…glutamicum. , In addition, through multilevel metabolic engineering strategies, the putrescine titer of the engineered Bacillus amyloliquefaciens increased to 6.76 g/L from biomass hydrolysate Latilactobacillus curvatus KP 3–4 isolated from Kabura-zushi produced 94 mM putrescine by adding ornithine as a precursor . Putrescine production by engineered Aureobasidium melanogenum has also been reported, and 33.4 g/L putrescine was produced from glucose and glutamate after 120 h fed-batch fermentation …”
Section: Introductionmentioning
confidence: 99%
“…19 Latilactobacillus curvatus KP 3−4 isolated from Kaburazushi produced 94 mM putrescine by adding ornithine as a precursor. 20 Putrescine production by engineered Aureobasidium melanogenum has also been reported, and 33.4 g/L putrescine was produced from glucose and glutamate after 120 h fed-batch fermentation. 21 Traditionally, D-glucose was used as an industrial raw material for a wide range of chemicals production by C. glutamicum.…”
Section: ■ Introductionmentioning
confidence: 99%